An Analysis of Communication Strategies of Salatiga Municipality on Instagram during the Covid-19 Pandemic - Wijaya, Lina Sinatra; Lattu, Izak Y. M.; Davianti, Arthik (Jurnal The Messenger, 2022)
Introduction: Covid-19 cases in Indonesia reached their peak in mid-June 2021. The peak has caused all city governments in Indonesia to provide accurate and reliable information for all the citizens in tackling the spread of the virus. Salatiga is one of the city governments that successfully handled this condition. Therefore this study will analyze the communication strategies the Salatiga City Government used to disseminate information to the public via Instagram.Methods:This study uses a qualitative analysis approach to assess the content of the text data and information related to coronavirus published on the Instagram of Salatiga Municipality, called: @humaskotasalatiga.Findings: This study found that in implementing the strategies, the Salatiga City Government used six principles of System Theory: system transformation, openness, interdependence, negative entropy, equifinality, and requisite variety. This study also recommends that the Salatiga City Government communicate information clearly and honestly, organize information management for government leaders and government officials to provide the most up-to-date information, and construct comprehensive governmental health risk communication systems.Originality: Many studies have been done on communication strategies by Salatiga Municipality. However, no study analyzes the communication strategies used by Salatiga Municipality, primarily through Instagram, during the pandemic. Therefore, this study analyzes how Salatiga Municipality the communication strategies through Instagram.